Accounts and Images of Six Kannon in Japan, by Sherry Fowler. - Astley, Ian (Buddhist Studies Review, 2018)
Accounts and Images of Six Kannon in Japan, by Sherry Fowler. University of Hawai’i Press, 2016. xx + 411pp., 27 colour plates. Hb. $70 (£74.50). ISBN-13: 9780-824856229.